2022
DOI: 10.1002/aff2.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented corn protein concentrate on growth performance, haemocyte counts, histological structure of hepatopancreas and intestinal condition of pacific white shrimp Litopenaeus vannamei

Abstract: This study evaluated the suitability of commercially produced fermented corn protein concentrate (FCPC) known as MOTIV® (Cargill's IP Product), in replacing fishmeal (FM) and/or poultry by‐product meal (PBM) on growth and health performances of the Pacific white shrimp Litopenaeus vannamei. A 60‐day feeding trial was conducted to evaluate the use of five iso‐nitrogenous and iso‐lipidic diets containing 0% FCPC (control), 7.5% FCPC and 1.5% Krill meal (KM) replacing 9% of FM (FCPC 1), 7.5% FCPC and 1% KM replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…In shrimp, the hepatopancreas is the major digestive gland within a complex arrangement, and also a sensitive organ to the change in feed ingredients, and consequently is an essential indicator for metabolism [42,43]. It was reported that a low dosage of tannins had positive effects on the digestion and absorption [44], including shrimp P. vannamei [21].…”
Section: Discussionmentioning
confidence: 99%
“…In shrimp, the hepatopancreas is the major digestive gland within a complex arrangement, and also a sensitive organ to the change in feed ingredients, and consequently is an essential indicator for metabolism [42,43]. It was reported that a low dosage of tannins had positive effects on the digestion and absorption [44], including shrimp P. vannamei [21].…”
Section: Discussionmentioning
confidence: 99%